Gideon falls, book two ebook - Lemire, Jeff (Gideon Falls (2018), 2022)
A brand-new ongoing series from the acclaimed bestselling creative team of Old Man Logan and Green Arrow! The lives of a reclusive young man obsessed with a conspiracy in the city's trash, and a washed-up Catholic priest arriving in a small town full of dark secrets, become intertwined around the mysterious legend of The Black Barn, an otherworldly building that is alleged to have appeared in both the city and the small town, throughout history, bringing death and madness in its wake. Rural mystery and urban horror collide in this character-driven meditation on obsession, mental illness, and faith.